Competence of Shadow Teacher in Building Confidence and Life Skills of Students with Special Needs - Sahnan, Ahmad; Purwasih, Wahyu; Wiyani, Novan Ardy (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study aims to describe the competencies of shadow teachers in developing the confidence and life skills of children with special needs at elementary school. The research method used is a qualitative descriptive research method with a phenomenological type. Data is collected through observation, interviews, and documentation. The study results show that shadow teachers have four competencies in building confidence and life skills. 1) Professional competence. Teachers improve professional competence by participating in training related to inclusion education online and offline; 2) Pedagogical competence. Teachers make individual learning programs based on the results of assessments carried out by psychologists, learning using a pullout system, children with special needs do the same learning as regular children, teachers always include children with special needs in school activities, three and social competence. Teachers include social relations with parents, social relations with experts (pediatricians and psychologists), social relations with children with special needs, social relations with regular children, and social relations between teachers; 4 and personal competence. The personal competencies of shadow teachers include being a special assistant teacher as a calling, patient and diligent, sincere, empathetic, fair, a spirit of learning, and having a high sense of affection